Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Pratique # 17 : Les séances de dialogue au Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)